An approach to interpreting restrictive spirometric pattern results in occupational settings - Tafuro, Federica; Corradi, Massimo (La Medicina del Lavoro, 2016)
Objectives: The aim of this review is to provide an updated overview of definition, epidemiology, diagnostic algorithm and occupational exposures related to abnormal restrictive spirometrical pattern (RSP) in order to improve the correct interpretation of spirometry test results by occupational healthcare providers. Methods: A review of the scientific English literature of the last 25 years was carried out with MEDLINE and related keywords [(restricti* AND spirometr*) AND occupational]. The first step analysis covered 40 studies and the second step the reference list. Results are presented in four major aims and subquestions. Results: A spirometrical pattern of reduced VC (Vital Capacity), together with a normal FEV1 (Forced Expiratory Volume in 1 Second)/VC ratio, is suggestive, though not diagnostic of restrictive ventilatory defect (RVD). The prevalence of RSP is high in some studies, comparable to obstructive pattern, and could be associated to chronic medical conditions (diabetes, congestive heart failure, obesity, hypertension) as well as to increased risk of mortality and lung cancer. In order to predict true restrictive defect [TLC-(Total Lung Capacity)